ANALISIS USAHA PANEN CENGKEHDI KABUPATEN MINAHASA TENGGARA PROPINSI SULAWESI UTARA - Nelson H. Kario (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2014)
Currently, clove is important plantation crop due to its high price (Rp 85.000 at harvest and Rp 135.000 at dry condition), although at late 1990s it was only Rp 3500 per kg. Then, many clove crops were left died with bad cultivation, cut, and even made as firewood. In relation to free trade area, clove cigarette development, great cigarette excise and source of employment, government gives increasingly great attention. Then, as main commodity of national economy, clove cultivation is important matter included harvest and post harvest process because it will affect quality and selling price. Objectives of the research was to study cost structure of harvest and post harvest, to identify harvest and post harvest cost effect on income, and to analyze feasibility of clove cultivation business. The research was done for 2 months from August to September 2013. Location was determined using purposive sampling involving 20 farmers. Data include primary and secondary data that was analyzed descriptively. The results indicated that harvest cost was very high covering 80.33% of total cost in clove cultivation cost; harvest and post harvest cost has effect of 20.92% on revenue and 26.46% on income. This clove cultivation is feasible financially because it is economically profitable with B/C ratio of 3.77. Keywords: clove, farming system, price, labour, farmer